2019
DOI: 10.1088/1742-6596/1393/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Unipolar and bipolar mode of deep oscillation magnetron sputtering

Abstract: The paper presents the results of a study of the modes of dual deep oscillation magnetron sputtering. The use of packet pulse discharge power supply allowed to provide a high power density on the surface of the Al target 60–500 W·cm−2 and the ion current density on the substrate 4–20 mA·cm−2 during the duration of the macro pulse – 1 ms. In addition to the parameters of a pulsed power supply, the way of connecting the power source to the dual magnetron sputtering system and the vacuum chamber changed during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Важными достоинствами обладают дуальные МРС, которые питаются переменным током. Они решают проблему потери анода и позволяют увеличить ионное воздействие на растущее покрытие по сравнению с одиночными МРС [8]. Ионная бомбардировка подложки в процессе напыления является эффективным инструментом управления энергией, передаваемой покрытию.…”
Section: Introductionunclassified
“…Важными достоинствами обладают дуальные МРС, которые питаются переменным током. Они решают проблему потери анода и позволяют увеличить ионное воздействие на растущее покрытие по сравнению с одиночными МРС [8]. Ионная бомбардировка подложки в процессе напыления является эффективным инструментом управления энергией, передаваемой покрытию.…”
Section: Introductionunclassified
“…Both of these techniques have been proposed as new methods to increase the deposition rate by avoiding arcs in DOMS and reducing metal ion back-attraction in m-HiPIMS. Furthermore, very recently, bipolar-DOMS has been developed as a new method that combines the elements of DOMS and m-HiPIMS [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that in some cases of high-power pulsed reactive sputtering processes, the hysteresis effects tend to mitigate, thus alleviating the requirements for gas supply control systems, while in others they do not appear at all [24,27,28], which is beneficial for coating deposition applications. However, the challenges for stable efficient deposition processes of high-quality compound (and especially transparent oxide) thin films still remain and stimulate refining of the pulsed magnetron techniques as well as developing of the novel ones [e.g., deep oscillation magnetron sputtering (DOMS) [29][30][31][32][33]].…”
Section: Introductionmentioning
confidence: 99%